Business Ethics and Corporate Governance: A Global Perspective - Banik, Gour Gopal (Prabandhan: Indian Journal of Management, 2010)
It is only in the recent years that Business Ethics and Corporate Governance have become almost a public issue and have started getting favourable responses from the corporations, government agencies, shareholders, employees, suppliers, customers, competitors, the news media, community residents etc. i.e. the entire society. In fact, business ethics and corporate governance go hand in hand. With the growing strength of consumer movements and rising levels of awareness among stakeholders, corporations are realizing that stakeholders and consumers are no longer indifferent to unethical practices like financial irregularities, tax-evasion, poor quality products and services, non-compliance with environmental issues, and hazardous working conditions. Companies have now begun to integrate ethics into their corporate cultures and concentrate on putting appropriate corporate governance mechanisms in place."Unethical practices may contribute to immediate gain but always at the cost of future prospects." (Shastri, 2005). Corporate corruption scandals have increased drastically over the last few years throughout the world. Business Ethics are more forceful, more influential, more effective and even more helpful in corporate governance than the anti-corruption programs; as the Institute Of Business Ethics, UK does rightly have the motto: "Doing Business Ethically. Makes For Better Business."